Irish Landscape and National Identity in 20th-century Literature - Loubová, Barbora (Univerzita Pardubice, 2022)
This thesis focuses on portrayal of landscape as a tool for strengthening the Irish national identity. The goal of the theoretical part is to introduce general terms such as landscape and national identity. The practical part is divided into two chapters with the analysis of particularly chosen Irish books. The main aim of the paper is to analyse the texts by Tomás O'Crohan, Maurice O'Sullivan and J. M. Synge.
Irská krajina a národní identita v literatuře 20. století
Keywords: landscape; national identity; nationalism; patriotism; krajina; národní identita; nacionalismus; patriotismus